Effects of multiple intelligences instruction and strategies on writing ability of ESL students - Looi, Lin Eng (2011)
The surge of research in the field of multiple intelligences since it was introduced by Howard Gardner in 1983 and the encouraging results based on these research show that the Theory of Multiple Intelligences is gaining importance in improving the academic performance of students in various disciplines. There is an increasing number of research which applies the Theory of Multiple Intelligences in the teaching of English. However, at present there is no quantitative research in Malaysia applying the Theory of Multiple Intelligences to developing writing skills in ESL. As writing is a complex skill, most of the time getting ESL students to write is an uphill task. The fear for writing maybe due to the many problems that ESL writers faced which include difficulty in generating ideas, visualizing ideas, arranging ideas,lack of vocabulary and cohesion and coherence in writing. With this in mind, the research was developed based on the three theories namely, the Theory of Multiple Intelligences (Gardner, 1983), Triarchic Theory (Sternberg, 1985) and the Vygotsky Learning Theory (Vygotsky, 1986). This study which involves a group of Form One students was conducted to determine the effect of multiple intelligences instruction and strategies on their writing ability. Five intelligences related to writing were identified: interpersonal intelligence, visualspatial intelligence, logical-mathematical intelligence, verbal-linguistic intelligence,and intrapersonal intelligence. The Malaysian Multiple Intelligences Test for Adolescents (MAMIT) was administered to the students to identify the intelligence(s) that the students had developed more highly. The experimental class, which comprised 28 students was then divided into groups of five. Students with different intelligences were assigned to each group. Each group consisted of students with different profiles of the five intelligences related to writing. The experimental class was given training for two months while the control class was taught in the usual way using the normal curriculum and no particular additional method was used with these students. The two-month training was divided into two parts. In the first part, which was the Intelligence-Focused Lessons, students were given a specific training programme of teaching which strongly encouraged the development of the five intelligences related to writing. In the second part, which was the 5-in-1 Lesson, students were taught the five multiple intelligences strategies related to writing. The five strategies were brainstorming, topic-word association, mind-mapping, rank-ordering, and metacognition. Students were then asked to apply these strategies in their writing. Two essays, one narrative and another expository, were given to the students before and after the training. The control group was also given the same essay topics as the experimental group. The difference between the two groups was that the experimental group went through the two phases of multiple intelligences training while the control group did not. The scoring of the essays was done using the Six-Trait Analytic Writing Rubric, which consisted of Ideas, Organization, Voice, Word Choice, Sentence Fluency and Conventions. The scores were analyzed using Paired Samples t-test and MANOVA. The results show that there is a significant improvement in the essays of students in the post-test compared to those in the pre-test. There is also improvement in the six rubrics analyzed. Both the experimental group and the control group show improvement as they were exposed to English lessons during the two months. The difference is, the experimental group shows great improvement which, it is concluded, is highly likely to be attributed to the multiple intelligences instruction and strategies. A retention test was carried out with the two groups after a month and significant improvement was detected in the experimental group. The results of the study support the Theory of Multiple Intelligences, which implies that students should be exposed to multiple ways of learning according to their needs and abilities. In a classroom, teachers should recognize that students have different interests and needs and teaching instruction should be varied to suit them. This research shows that given, first, exposure to a variety of methods relating to multiple intelligences and second, encouragement to develop appropriate strategies related to the process approach to writing, it is possible for learners to improve their writing ability significantly in the six traits measured and this can be retained at least for a month.